The influence of turmeric supplementation in feed on the growth performance of Asian Redtail Catfish (Hemibagrus nemurus) - Rahmadani Siagian Desi; Suharman Indra; Fatmawati Riska; Rangkuti Putra (BIO Web of Conferences)
Asian redtail catfish farming faces challenges with low seed production, necessitating improved feeding strategies to boost production. Antioxidants, such as those found in turmeric, are considered crucial feed ingredients. This research investigated the impact of turmeric-enriched feed on the growth performance of Asian redtail catfish. Five experimental treatments were formulated with varying turmeric concentrations: P1: 0.0 g kg-1 feed, P2: 0.5 g kg-1 feed, P3: 1.0 g kg-1 feed, P4: 1.5 g kg-1 feed, P5: 2.0 g kg-1 feed; each treatment had three replications. 20 juveniles of Asian redtail catfish were reared in 10-liter aquariums. The study duration was 55 days. Fish were fed to satiation three times a day (8:00 AM, 1:00 PM, 6:00 PM). Turmeric-supplemented diets resulted in increased final body weight, greater absolute length, higher specific growth rate, enhanced feed intake, and improved feed conversion ratio. Meanwhile no significant differences were observed in feed efficiency and survival rate. The study demonstrates that incorporating turmeric into the feed can effectively promote growth in Asian redtail catfish. These findings suggest that turmeric supplementation could be a valuable strategy for improving production in Asian redtail catfish culture.